ADVANCED MATHEMATICAL MODEL OF THE CENTRIFUGAL REGULATOR OF THE WIND ROTOR WITH FLUGE CONTROL - Golovko, V.; Kokhanievych, V.; Shykhailov, M.; Marchenko, N. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2021)
Centrifugal regulators have become widespread in various fields of mechanical engineering and instrumentation for regulating and measuring the speed of mechanisms and motors. The most fundamental studies in this field are the works of N.E. Zhukovsky, I.O. Vyshegradsky, A. Stodola, and others. In the further development and generalization of the theory of centrifugal regulators acquired in the work of L.M. Tsukernik. For wind turbines, G.H. Sabinin proposed a centrifugal regulator scheme for weather vane control ГС-4 and was implemented in a number of installations, namely BЭ-2, BЭ-3, BЭ-5. A number of studies of such control systems were conducted at the Storm Design Bureau at NTUU KPI, and later at the Institute of Electrodynamics of the National Academy of Sciences of Ukraine. The Institute of Renewable Energy proposed an improved scheme of the ГС-4 regulator and a corresponding mathematical model, namely, a variable angle between the blade chord and the axis of moment of inertia of centrifugal weights was introduced (in the ГС-4 regulator it was constant and was 90°). If at the beginning of the development of wind power, technological capabilities made it possible to obtain a trapezoidal blade shape without geometric twisting of the chord (or with insignificant up to 4°...5°), then in mathematical models it was legitimate to assume that the direction of the moment of inertia of the blade coincides with the chord of the blade. Today, the trend in the manufacture of a blade is aimed at obtaining the maximum utilization of wind energy by the rotor and, accordingly, the maximum approximation of the real blade profile to the calculated one. That is, in modern blades, blade expansion from end to butt is used in the range from 1:2 to 1:4, and the twisting of the chordi of the blade reaches 30°. Considering all this, it can be stated that the deviation of the direction of the moment of inertia of the blade from the chord of the blade can be up to 20°. Therefore, without taking into account this angle, the mathematical models of the centrifugal controller are not perfect enough. In this paper we propose a mathematical model of the centrifugal regulator of the wind turbine rotor taking into account the angle between the vector of the moment of inertia of the blade and its chord, which allowed to obtain a refined expression for the static characteristics of the regulator speed of the wind turbine rotor. Bibl. 11, fig. 1.